Rethinking Sustained Competitive Advantage from Human Capital - Campbell, Benjamin A.; Coff, Russell; Kryscynski, David (Academy of Management Review, 2012)
The strategy literature often emphasizes firm-specific human capital as a source of competitive advantage based on the assumption that it constrains employee mobility. We first identify three boundary conditions that limit the applicability of this logic. We then offer a more comprehensive framework of human capital–based advantage that explores both demand- and supply-side mobility constraints. The critical insight is that these mobility constraints have more explanatory power than the firm specificity of human capital.